2019
DOI: 10.1021/acs.jpca.9b09655
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Hydrogen Bond Interaction Dynamics in the Guanine and Cytosine Crystals: Ab Initio Molecular Dynamics and Spectroscopic Study

Abstract: In this work, we present the comparison study of guanine and cytosine crystals based on the hydrogen bond (HB) dynamics. The ab initio molecular dynamics gave us a base for detailed analysis. The analysis of the trajectories by power spectrum generation, as well as the fluctuation of the interaction energies, showed large differences between HB networks in the considered crystals. The charge flow is present in the guanine molecule which forms the flat surfaces in the crystals. In the cytosine zigzag structure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…These signals originate from multiple hydrogen bonds present in the studied system. These bonds differ in their length, energy, spectroscopic frequency, and intensity, as shown in previous works [31][32][33][34]. Similar to the spectroscopic method results, the PXRD patterns (Figure 10) of the complexes are quite similar, with the exception of LYS.…”
Section: Atom Numbersupporting
confidence: 85%
See 1 more Smart Citation
“…These signals originate from multiple hydrogen bonds present in the studied system. These bonds differ in their length, energy, spectroscopic frequency, and intensity, as shown in previous works [31][32][33][34]. Similar to the spectroscopic method results, the PXRD patterns (Figure 10) of the complexes are quite similar, with the exception of LYS.…”
Section: Atom Numbersupporting
confidence: 85%
“…These signals originate from multiple hydrogen bonds present in the studied system. These bonds differ in their length, energy, spectroscopic frequency, and intensity, as shown in previous works [31][32][33][34].…”
Section: Atom Numbersupporting
confidence: 68%
“…The NVT ensemble method seems typical one of such methods. 58 The predicted nature will change depending on the quality of the calculation levels, especially for weak HBs. However, the results in the framework of QTAIM-DFA with CIV should be reasonable, if calculated with MP2/BSS-B 0 a.…”
Section: Structural Feature In the Perturbed Structures Of Nu-numentioning
confidence: 99%
“…14,15 In addition, charge transfer promotes strong hydrogen bonding between G and C, giving G–C a stable planar structure. 16 Recent work has confirmed that the electron excited state is the charge-transfer state of G–C coexisting with the Frenkel exciton state of C. 17 It can evaluate and regulate the genetic damage caused by photoreactions in DNA. The rate of charge-transfer is closely related to the degree of DNA photodamage.…”
Section: Introductionmentioning
confidence: 99%